Study of medicines’ market for the treatment of seborrheic dermatitis of the pilar part of head - V. A. Solodovnik; N. O. Tkachenko; S. А. Gladisheva; Fadi Al Zedan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Modern arsenal of medicines and cosmetics used for the therapy of seborrheic dermatitis of the pilar part of head is various enough. Today pharmaceutical market keeps developing and constitutes a complex system that causes the necessity of its investigation and forming the informational base concerning the dynamics of assortment, prices and availability of medicines.